2014
DOI: 10.1371/journal.pone.0080836
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Bcl-2/Bcl-XL Induces Antitumor Activity in Uveal Melanoma Patient-Derived Xenografts

Abstract: PurposeUveal melanoma (UM) is associated with a high risk of metastases and lack of efficient therapies. Reduced capacity for apoptosis induction by chemotherapies is one obstacle to efficient treatments. Human UM is characterized by high expression of the anti-apoptotic protein Bcl-2. Consequently, regulators of apoptosis such as Bcl-2 family inhibitors may constitute an attractive approach to UM therapeutics. In this aim, we have investigated the efficacy of the Bcl-2/Bcl-XL inhibitor S44563 on 4 UM Patient-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 46 publications
1
23
0
1
Order By: Relevance
“…However, patient-derived xenograft (PDX)-based mouse studies with uveal melanoma tumors by Nemati et al have brought into focus alternative approaches of developing targeted therapy. 107 Those authors used well characterized PDX from primary uveal melanoma in mice to study the effect of small-molecule inhibitors of B-cell lymphoma-2/ B-cell lymphoma-extra large (Bcl-2/Bcl-XL) on uveal melanoma tumor growth. Primary uveal melanoma reportedly has high expression of the antiapoptotic protein, Bcl-2.…”
Section: Translational Approachesmentioning
confidence: 99%
“…However, patient-derived xenograft (PDX)-based mouse studies with uveal melanoma tumors by Nemati et al have brought into focus alternative approaches of developing targeted therapy. 107 Those authors used well characterized PDX from primary uveal melanoma in mice to study the effect of small-molecule inhibitors of B-cell lymphoma-2/ B-cell lymphoma-extra large (Bcl-2/Bcl-XL) on uveal melanoma tumor growth. Primary uveal melanoma reportedly has high expression of the antiapoptotic protein, Bcl-2.…”
Section: Translational Approachesmentioning
confidence: 99%
“…The comparison of serial UM xenografts to the original tumor showed that xenografts are genetically stable over in vivo passages and maintain the genetics features of the original human UM [382]. Despite the limits of a low rate of engraftment and growth delay after initial transplantation, panels of UM PDXs have been employed to test combinations of targeted therapies [383, 384]. …”
Section: Animal Modelsmentioning
confidence: 99%
“…BM-1197 caused reversible platelet reduction in mice at highly efficacious doses. Servier also generated a nanomolar affinity dual BCL-2/BCL-X L inhibitor, S44563, which exerted promising inhibitory efficacy in patient-derived uveal melanoma cell lines and xenografts and enhanced sensitivity of small cell lung cancer to radiation [21,22]. …”
Section: Bh3 Mimetics Of Anti-apoptotic Bcl-2 Proteinsmentioning
confidence: 99%